„Ogień i piasek” — o ostatnim okresie życia i twórczości Norwida na podstawie elegii Na zgon Poezji - Grabowski, Mateusz (Starość i młodość w literaturze i kulturze, 2016)
The purpose of this article is to analyse one of the leastknown works of the poet — the elegyNa zgon Poezji. This is the one of the last three Norwid’s works, and, moreover, the first which isopening the last period of Promethidion’s author writings. Abandoned, condemned to poverty andobscurity poet is experiencing a period of deep collapse, which, however, doesn’t permit him to staysilent. By reference to Norwid’s works, correspondence and biography the author of this paper willtry to reconstruct the least known phase of his life – the residence in the shelter of St. Casimir inIvry.